Effects of virginiamycin or monensin plus tylosin on ruminal fermentation characteristics in steers fed dry-rolled corn with or without wet corn gluten feed - Ives, S.E.; Del Barrio, A.; Bindel, D.J.; Titgemeyer, Evan C.; Nagaraja, Tiruvoor G. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A study was conducted to evaluate effects of virginiamycin and monensin plus tylosin on ruminal fermentation characteristics in steers fed dry rolled corn-based finishing diets with or without wet corn gluten feed. Ruminal pH was higher, concentrations of volatile fatty acids were lower, and ciliated protozoal numbers were higher in steers fed diets with wet corn gluten feed. Including virginiamycin or monensin plus tylosin had few effects on the ruminal fermentation characteristics we measured. Including wet corn gluten feed appeared to stabilize the ruminal fermentation.
Keywords: Beef; Steers; Rumen fermentation; Virginiamycin; Monensin; Corn gluten feed